1996
DOI: 10.1111/j.1532-5415.1996.tb02428.x
|View full text |Cite
|
Sign up to set email alerts
|

1H‐MRS, MRI‐Based Hippocampal Volumetry, and 99mTc‐HMPAO‐SPECT in Normal Aging, Age‐Associated Memory Impairment, and Probable Alzheimer's Disease

Abstract: These findings support the hypothesis of a continuum among the three conditions studied, or at least between AAMI and DAT, where AAMI seems to be an early, monosymptomatic stage of Alzheimer disease. Accepting this view, it would be questionable to maintain the term "age-associated memory impairment" as a discrete entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
2

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 25 publications
2
59
1
2
Order By: Relevance
“…These data also support the concept that an elevation in MI /Cr is evident prior to the full clinical manifestations of AD. However the criteria used for the diagnosis of age associated memory impairment are different from criteria used in our study for MCI 10 .…”
Section: Myo -Inositol / Creatine Ratiosmentioning
confidence: 71%
See 3 more Smart Citations
“…These data also support the concept that an elevation in MI /Cr is evident prior to the full clinical manifestations of AD. However the criteria used for the diagnosis of age associated memory impairment are different from criteria used in our study for MCI 10 .…”
Section: Myo -Inositol / Creatine Ratiosmentioning
confidence: 71%
“…Anatomic neuroimaging studies of MCI patients have been published 23 . Although, biochemical alterations have been shown in the brains of patients with age associated memory impairment 10 , to our knowledge, there are no published data specifically addressing the 1 H MRS findings in MCI patients.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Also, we did not include age-matched control subjects without Alzheimer's disease, which would have allowed us to test the hypothesis that Alzheimer's disease is associated with higher choline/creatine ratios at baseline. Although some studies have indicated high ratios (4,14), others have not (15,16). MRS was performed by using only a single brain voxel, but a reproducible method was used to standardize its placement and enhance reliability of the metabolite resonances.…”
Section: Discussionmentioning
confidence: 99%